Lives on hold: Prospective international students and the #JapanTravelBan - Brotherhood, Thomas (Journal of International Students, 2023)
This paper analyses Japan’s COVID-19 response drawing on a survey of more than 3200 prospective international students affected by the (colloquially named) #JapanTravelBan. The paper charts the evolution of Japan’s COVID-19 response from the earliest border restrictions in February 2020 to the eventual blanket re-opening to international students in Summer 2022. Subsequently, survey DATA provide evidence of (1) the drastic mental health effects for prospective international students during this time, (2) students’ loss of agency due to the protracted uncertainty of both policy and communication from the Japanese government, and (3) potential damage caused to Japan’s reputation as a study destination. Drawing on these findings the paper offers broader suggestions for appropriate student migration policymaking: greater transparency, attention to students’ security throughout their study sojourn, an emphasis on stability, and resilience to crises.